(untitled) (Journal of Psychiatrists’ Association of Nepal, 2023)
Attention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder characterized by age inappropriate levels of inattention, and or impulsivity and hyperactivity. Often arising in childhood, ADHD can also be chronic in nature, frequently continuing through adolescence and beyond, at least at the level of impairment. The early accurate diagnosis of the condition is possible based on clinic settings, clinicians’ expertise; and the context at which screening and evaluation of this population for ADHD is done. ADHD is an etiologically complex neurodevelopmental disorder that begins early in life and has heterogeneous clinical manifestations encompassing a broader spectrum of psychopathology. This underscores the importance of early accurate diagnosis so that effective treatments can be started that significantly reduces immediate and long-term psychosocial burdens. Effective ADHD treatments are available and cognitive neuroscience is rapidly expanding, however there is a significant gap between empirical evidence and clinical practice. Multimodal and multidisciplinary treatment strategies are the best approach in the treatment, but there is a significant gap between the knowledge and practice, such that evidence-based treatments are often not implemented in the community settings. How we implement such in our clinical practice helps us to advocate and advance towards more effective ADHD treatments. There is growing scientific progress in understanding the causes and treatment of ADHD. Knowledge about the evidence-based recent advances in the treatment helps mental health professionals to advocate for the effective approaches to treat ADHD, with minimal unwanted side effects.